Catalytic Activity of Chloro and Triflate Manganese(II) Complexes in Epoxidation Reactions: Reusable Catalytic Systems for Alkene Epoxidation. Issue 16 (12th May 2014) - Rich, Jordi; Manrique, Ester; Molton, Florian; Duboc, Carole; Collomb, Marie‐Noëlle; Rodríguez, Montserrat; Romero, Isabel
Abstract: The catalytic oxidation of a series of alkenes by three Mn II complexes, MnCl2 [(–)‐L]2 (1 ), ({MnCl[(–)‐L]}2 (μ‐Cl)2 ) (2 ), and Mn(CF3 SO3 )2 [(–)‐L]2 (3 ), having the bidentate N‐ligand (–)‐pinene[5, 6]bipyridine, (–)‐L, and using peracetic acid as oxidant in acetonitrile is described. The performance of catalysts1 and2 is enhanced by the use of additives (NaHCO3 and imidazole) and also using a [bmim]/acetonitrile mixture as reaction media. The latter conditions allow recyclability of the catalytic system, keeping good selectivity and conversion values in some cases. The nature of the species formed in acetonitrile after the addition of peracetic acid has been investigated through EPR and UV/Vis spectroscopy. The results point to the formation of high‐valent manganese species, among which a di‐μ‐oxo‐bridged Mn2 (III, IV) binuclear species was unambiguously identified for complex3 through a typical 16‐line EPR signature. Abstract : The epoxidation activity of mononuclear Mn complexes with peracetic acid has been tested in CH3 CN and in ionic liquid/CH3 CN media. The latter conditions allow recyclability of the catalytic systems for several substrates keeping good selectivity and conversion values for up to 7–9 runs.